Globalization of World Politics - Baylis, John.( ed.) (Oxford, 2001)
Fully revised and updated to cover the latest developments in world politics, the second edition of this highly successful textbook will once again provide the ideal introduction for all students of International Relations. Written specially for those coming to the subject for the first time, this text has been carefully edited by John Baylis and Steve Smith to ensure a coherent, accessible, and lively account of the globalization of world politics. The book is accompanied by a dedicated COMPANION WEBSITE - including PowerPoint slides; further questions, web links, and case studies that put theory into practice with analysis of real life issues. NEW TO THIS EDITION: Updated to reflect events since 1997, with more attention given to the integration of the globalization theme throughout the book. The HISTORY section now has a new chapter by Michael Cox on 'International History since 1990' bringing the story of International Relations up to the present day. The THEORY section has been significantly reorganized following feedback from teachers and includes a new chapter on 'Contemporary Mainstream Approaches' by Steve Lamy. The new organization of this section allows more room to introduce to the main theories of International Relations (such as realism and liberalism) and to explain complex theoretical developments in more detail. The INTERNATIONAL ISSUES section now includes a chapter on 'The Communications and Internet Revolution in IR' by Jonathan Aronson and a substantially revised chapter on 'Culture in World Affairs' by Simon Murden. The book also includes new contributions on International Political Economy (Ngaire Woods) and European Integration (Thomas Christiansen). NEW concluding section on 'Globalization in the Future': this new final section contains two chapters by leading International Relations scholars - Andrew Linklater on 'Globalization and the Transformation of Political Community' and Ian Clark on 'Globalization and the Post-Cold War Order'.
Keywords: Foreign Relations